2020
DOI: 10.1111/ppc.12674
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress among midwifery students

Abstract: Purpose: This study aimed to examine the factors affecting secondary traumatic stress on midwifery students.Design and Methods: This descriptive study was conducted between November and December 2018. Data were collected using information form and the Secondary Traumatic Stress Scale.Findings: The study found that 22.2% of midwifery students met all the trauma criteria for posttraumatic stress disorder according to the Secondary Traumatic Stress Scale. Midwifery students who were unhappy to continue their educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…However, there are factors such as loss of control, inability to cope with pain, various complications and traumatic birth that can turn the childbirth process into a stressful and traumatic experience [ 80 , 81 ]. A recent study showed that midwifery students were facing a high level of STS rates which should be supported by mental health nurses to cope with traumatic stress [ 82 ]. However, further studies should explore the difference between midwifery and nursing interns.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are factors such as loss of control, inability to cope with pain, various complications and traumatic birth that can turn the childbirth process into a stressful and traumatic experience [ 80 , 81 ]. A recent study showed that midwifery students were facing a high level of STS rates which should be supported by mental health nurses to cope with traumatic stress [ 82 ]. However, further studies should explore the difference between midwifery and nursing interns.…”
Section: Discussionmentioning
confidence: 99%
“…Most health care providers, such as palliative care providers, hospice health care practitioners, physicians, midwives, nurses, and nursing students, are at risk of developing compassion fatigue [ 5 ]. Although compassion fatigue has been studied extensively in the nursing profession, few studies have been conducted among nursing or midwifery students [ 6 , 7 ]. Care providers appear to be especially sensitive and susceptible during this period of transition from student to professional [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They may feel defenseless and worn out due to the heavy emotional burden of their occupational responsibilities, and in the case that they are not able to effectively cope with secondary stress, the care they provide may be affected negatively. The stress caused by such traumas affects the workplace negatively, reduces the feeling of compassion in the care process, decreases the quality of care, and causes loss of motivation and burnout ( Bayri Bingol et al, 2020 ). The symptoms of secondary traumatic stress are similar to those of posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%